LKPD Model Inquiry Based Learning Terintegrasi STEM : Analisis Kebutuhan - Restu Vanni Dezola; Edi Istiyono; Insih Wilujeng (Postgraduate, University of Mataram, 2023)
The research aimed to determine teaching materials that matched the characteristics of students to provide a stimulus to critical thinking skills to solve problems in learning science. In science learning, critical thinking is an important basic competency because it is a skill developed through an educational process that begins with analyzing classroom problems, analyzing curriculum, analyzing student characteristics, and analyzing natural science learning resources. The research conducted is descriptive qualitative. Researchers describe the data obtained related to the object to obtain conclusions. Researchers apply the interactive model put forward by Miles and Huberman including data reduction, data presentation, and drawing conclusions. The subjects of this study included class VIII students at SMPN 5 Padang. Data collection was carried out through interviews with teachers and student observation in order to obtain information related to student characteristics, learning models, and views on students' needs in teaching materials. The findings show that students and teachers need learning tools in the form of student worksheets teaching materials to stimulate critical thinking skills using the STEM integrated inquiry based learning model.